2003
DOI: 10.1021/ja034662a
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Exploration of the 1,3-Dipolar Cycloadditions onto the Sidewalls of (n,n) Armchair Single-Wall Carbon Nanotubes

Abstract: The viability of 1,3-dipolar cycloadditions of a series of 1,3-dipolar molecules (azomethine ylide, ozone, nitrone, nitrile imine, nitrile ylide, nitrile oxide, diazomethane, and methyl azide) onto the sidewalls of carbon nanotubes has been assessed theoretically by means of a two-layered ONIOM approach. The theoretical calculations predict the following: (i) other than the 18-valence-electron azomethine ylide and ozone, the 16-valence-electron nitrile ylide and nitrile imine are the best candidates for experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 41 publications
(63 reference statements)
7
105
0
Order By: Relevance
“…[103] Moreover, all of these approaches have been assessed theoretically as means of purifying, opening sidewalls, and separating SWNTs diameter-specifically. [104,105] In addition, theoretical calculations [106] predict that nitrene and carbene (2 þ 1) cycloaddition reactions on narrow-diameter tubes can recover, as a consequence of bond cleaving, the ''ideal'' conductance of original pristine tubes. Metallic tubes subjected to covalent sidewall functionalization of CCl 2 experience a band gap opening as the functionalization concentration increases to 11% followed by a continuation of the bandgap trend with rising functionalization levels up to 33.3%.…”
Section: Organic Functionalization Strategiesmentioning
confidence: 99%
“…[103] Moreover, all of these approaches have been assessed theoretically as means of purifying, opening sidewalls, and separating SWNTs diameter-specifically. [104,105] In addition, theoretical calculations [106] predict that nitrene and carbene (2 þ 1) cycloaddition reactions on narrow-diameter tubes can recover, as a consequence of bond cleaving, the ''ideal'' conductance of original pristine tubes. Metallic tubes subjected to covalent sidewall functionalization of CCl 2 experience a band gap opening as the functionalization concentration increases to 11% followed by a continuation of the bandgap trend with rising functionalization levels up to 33.3%.…”
Section: Organic Functionalization Strategiesmentioning
confidence: 99%
“…Lu and co-workers studied the Diels-Alder reaction theoretically by means of the ONIOM approach. [43] They observed that the 1,3-butadiene addition to (5,5) carbon nanotubes was disfavored, but the cycloaddition of o-quinodimethane was feasible due to the aromatic stabilization of the adducts.…”
Section: Introductionmentioning
confidence: 99%
“…[43] They found that the addition of formoazomethine ylide to (5,5) SWCNT has a reaction energy of À39.3 kcal mol À1 and an activation barrier of 3.4 kcal mol 1.7 À21.7 17.8 26.5 C 60 [5,6] À34.4 1. , respectively (as compared to the B3LYP energies). This indicates that the use of the AM1 method as the low level method within the ONIOM approach leads to an underestimation of reaction and activation energies in comparison with the values obtained for the treatment of all atoms at the high level of theory.…”
mentioning
confidence: 99%
“…the constraints of the carbon skeleton are increasing with the decrease in diameters of nanotubes that can be detected with the increase of θ P values. 44 The influence of SWNT diameter on the ozonation of SWNT 45 which was studied theoretically ( Figure 13) has been confirmed by experimental observation of the main drawing of small-diameter nanotubes in the reaction of ozonolysis. Figure 13.…”
Section: The Estimation Of Fullerene Reactivity By Indices Based On Tmentioning
confidence: 65%